My child is God?s gift to humanity development and validation of the Parental Overvaluation Scale (POS). [article]. - Brummelman, Eddie; Thomaes, Sander; Nelemans, Stefanie A.
Although it is nature for parents to value their children, some parents ?overvalue? them, believing that their own children are more special and more entitled than other children are. This research introduces this concept of parental overvaluation. We developed a concise self-report scale to measure individual differences in parental overvaluation, the parental overvaluation scale (Study 1). The POS has high test-retest stability over 6, 12, and 18 months (Study 2). As demonstrated in a representative sample of Dutch parents (Study 3) and a diverse sample of American parents (Study 4), the POS has an internally consistent single-factor structure; strong measurement invariance across sexes; as well as good convergent, discriminant and criterion validity. Overvaluation is specially high in narcissistic parents (Studies 3, 4, 6). When parents overvalue their child, they overclaim their child?s knowledge (Study 4), perceive their child as more gifted than actual IQ scores justify (Study 5), want their child to stand out from others, and frequently praise their child in real-life settings (Study 6). By contrast, overvaluation is not consistently related to parents; basic parenting dimensions (i.e., warmth and control) or Big Five personality traits (Studies 3, 4, 6). Importantly, overvalued children are not more intelligent or better performing than other children (Studies 5-6). These findings support the validity of the POS and show that parental overvaluation has important and unique implications for parents? belief and practices. Research on overvaluation might shed light on the determinants of parenting practices and the socialization of children?s self-views, including narcissism. - - (from the authors)
Keywords: Parental overvaluation-Periodicals.; Parenting-Periodicals.; Narcissism-Periodicals.; Praise-Periodicals.